THE CRIME OF LIVING TOGETHER (KUMPUL KEBO) IN LAW NUMBER 1 OF 2023 CONCERNING THE CRIMINAL CODE IN LINK WITH THE REFORM OF CRIMINAL LAW IN INDONESI - Mulyana, Yusep (International Journal of Social Science, 2023)
Article 412 of Law Number 1 of 2023 concerning the Criminal Code regulates cohabitation or cohabitation. It reads: any person living together as husband and wife outside of marriage shall be punished with a maximum imprisonment of six months or a maximum fine of category II. Previously, cohabitation had not been regulated and only existed in the new Criminal Code. Its presence is to absorb the social, cultural and religious realities that exist in Indonesian society. So what was possible when we were in the village, classifying living together without marriage ties as something that is, say, inappropriate or reprehensible, in the new Criminal Code is trying to criminalize it. In a number of indigenous and tribal peoples, this kind of provision actually already exists. For example, in Bali there is something called lokika sanggraha